2014
DOI: 10.1080/03610918.2013.800205
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change Monitoring for Random Coefficient Autoregressive Time Series

Abstract: A monitoring scheme is proposed to sequentially detect a structural change in random coefficient autoregressive time series of order p (RCA(p)) after a training period of size T. It extends structural change monitoring to RCA(p) time series. The asymptotic properties of our monitoring statistic are established under both the null of no change in parameters and the alternative of a change in coefficient. The finite sample properties are investigated by a simulation study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In order of monitoring the financial trends modeled using the time series framework of ARMA-GARCH, A method was suggested by Doroudyan et al [5] on the basis of the Shewhart control chart. Tian et al [9] suggested a monitoring plan to identify a basic change in the randomized coefficient autoregressive model of time series of the order p (RCA(p)) in sequence, following the training duration of size T.…”
Section: Introductionmentioning
confidence: 99%
“…In order of monitoring the financial trends modeled using the time series framework of ARMA-GARCH, A method was suggested by Doroudyan et al [5] on the basis of the Shewhart control chart. Tian et al [9] suggested a monitoring plan to identify a basic change in the randomized coefficient autoregressive model of time series of the order p (RCA(p)) in sequence, following the training duration of size T.…”
Section: Introductionmentioning
confidence: 99%
“…Carsoule and Frances [4] considered a procedure based on maximum likelihood scores under normality assumptions and sketched some theoretical results. Quasi-maximum likelihood based monitoring in random coefficient autoregression was considered in Li et al [14], Na et al [17] and Prášková [18].…”
Section: Introductionmentioning
confidence: 99%